Design of energy efficient ventilation and air-conditioning systems - Brelih, Nejc (REHVA guidebook, 2012)
This guidebook covers numerous system components of ventilation and air-conditioning systems and shows how they can be improved by applying the latest technology products. Special attention is paid to details, which are often overlooked in the daily design practice, resulting in poor performance of high quality products once they are installed in the building system.